1998
DOI: 10.1007/s001340050573
|View full text |Cite
|
Sign up to set email alerts
|

Acute normovolaemic haemodilution does not aggravate gastric mucosal acidosis during cardiac surgery

Abstract: Acute normovolaemic haemodilution does not aggravate gastric mucosal acidosis during cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Two trials provided insufficient information about the volume of blood transfused intra‐ or postoperatively and were not included in most of the analyses 21,22 . Among the 34 trials comparing ANH to usual care, 11 trials were considered large‐volume hemodilution trials 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Two trials provided insufficient information about the volume of blood transfused intra‐ or postoperatively and were not included in most of the analyses 21,22 . Among the 34 trials comparing ANH to usual care, 11 trials were considered large‐volume hemodilution trials 22 .…”
Section: Resultsmentioning
confidence: 99%
“…30 Bacher et al found that intramucosal pH was better preserved in normovolemic hemodilution than in controls during cardiac surgery. 31 In hemorrhagic shock, Diebel et al demonstrated a normalization of intramucosal PCO 2 and pH after resuscitation, notwithstanding a hematocrit of 18 Ϯ 2%. 32 Finally, Layland et al showed that intramucosal pH was maintained during normovolemic hemodilution, despite reaching hemoglobin of 8.2 Ϯ 1.4 g/dL.…”
Section: Intramucosal-arterial Pco 2 Gap In Anemic Hypoxiamentioning
confidence: 98%
“…Of these 1,229 were excluded from further assessment at title and abstract screening, and 36 studies underwent full-text screening (Fig. Twelve studies did not report on our outcomes of interest (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). Excluded Studies.…”
Section: Characteristics Of Included and Excluded Studiesmentioning
confidence: 99%